INTERGROUP CONTACT AVOIDANCE IN INDONESIA - Pamungkas, Cahyo (Masyarakat Indonesia, 2018)
The objective of this study is to investigate the relationship between ethno-religious identification and the avoidance of intergroup contact between Muslims and Christians in Ambon and Yogyakarta with considering individual factors. Also, this study aims to fill the gap in literature between studies that emphasize economic and political contestation as the main sources of conflict and studies that focus on prejudice and discrimination as the causes of conflict. Lastly, this study focuses on examining ethnic group conflict theory, which is relevant to the analysis of ethno-religious conflicts in Western countries. The central research question is to what extent is there a relationship between ethno-religious identification among Christians and Muslims in Ambon and Yogyakarta, and avoidance of intergroup contact considering other individual-level determinants and particular intermediate determinants (salience of identity, perceived threats, intergroup contact, religiocentrism, attitudes toward religious plurality, interpretation of sacred writing, perceived discrimination, individual memory of violence, nationalistic attitudes, distrust, and social dominance orientation). I use both qualitative and quantitative methods as approaches to gathering and analysing data to support this study. The data collection methods included surveys, interviews, literature studies, and observations. Surveys were conducted among students at the undergraduate level with a minimum of second year standing from six universities in Ambon and Yogyakarta.